Integrated Ionic‐Additive Assisted Wet‐Spinning of Highly Conductive and Stretchable PEDOT:PSS Fiber for Fibrous Organic Electrochemical Transistors. (6th June 2021) - Chen, Yanping; Meng, Jie; Xu, Yiman; Li, Yaogang; Zhang, Qinghong; Hou, Chengyi; Sun, Hengda; Wang, Gang; Wang, Hongzhi
Abstract: As one of the most prevalently used conductive polymers, poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) has been studied for many years. Recently, especially with the development of smart clothing and wearable devices, PEDOT:PSS fiber is becoming the focus of researchers. However, the undesirable conductivity and stretchability hinder its applications. In this work, an integrated ionic‐additive assisted wet‐spinning strategy (IIAWS) is demonstrated to address the existing bottlenecks. The fabricated fiber exhibited an extremely high conductivity of 3573 S cm −1 and stretchability of about 30%. The mechanisms for conductivity enhancement in the entire preparation process are systematically studied and clarified. Furthermore, an all‐solid‐state fibrous organic electrochemical transistor (OECT) device based on the PEDOT:PSS fiber is fabricated with a transconductance of 2.44 mS and impressive bending property. Abstract : An integrated ionic‐additive assisted wet‐spinning strategy (IIAWS) is demonstrated for fabricating poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) fiber with high conductivity of 3573 S cm −1 and stretchability of about 30%, and the underlying mechanisms for conductivity enhancement by IIAWS are systematically investigated. Based on that, an all‐solid‐state fibrous organic electrochemical transistor (OECT) device is fabricated with excellent electrical performance and an impressive bending property.